'Tipping the balance' – an evaluation of COVID-19 parenting resources developed and adapted for child protection during global emergency responses. Issue 1 (31st December 2022) - Sherr, Lorraine; Mebrahtu, Helen; Mwaba, Kasonde; Nurova, Nisso; Chetty, Angelique Nicole; Swartz, Alison; Cluver, Lucie; Steventon Roberts, Kathryn J.; Lachman, Jamie M.
Abstract: Background: Parenting was severely affected by lockdown, school closure, illness, movement restrictions and the many sudden changes wrought by the global emergence of COVID-19. Responding to the need for a rapid emergency response to support parents and caregivers, a consortium of providers developed a suite of COVID-19 parenting resources based on evidence-based parenting interventions. Launched in March 2020, these were adapted for online use, with versions in over 100 languages, and the possibility for downloading, radio, and oral provision. A rapid qualitative evaluation initiative was conducted from September 2020 to February 2021 to inform the procedure, understand the impact and to drive future provision. Methods: The evaluation collected openended responses surveys (n = 495 participants) and in-depth interviews with parents, providers, and adolescent children (n = 22) from 14 countries and one global source. Data were gathered on parenting challenges during COVID-19 and the utility of the COVID-19 parenting resources. In-depth, semi-structured interviews explored the same concepts and elaborated on challenges, utility of the resources, and recommendations for the future. Data were coded in a hierarchy from basic, organising and global theme generation.Results: The parenting resources equipped parents with information and practices transforming everyday lives, and interactions. The tips provided prompts and permissions related to children's behaviour, enabled communications, and offered ways to reduce stress, monitor behaviour and navigate discipline challenges. The timeliness of the resources as well as the clarity and ease of use were seen as advantages. Future direction and possible hurdles related to adaptations needed according to recipient, child age, local context, culture, and new challenges. Conclusions: Overall findings point to the value and utility of this unprecedented global response to theCOVID-19 pandemic. Results suggest that rapid provision of parenting resources at scale is feasible and of use and opens a pathway for providing evidence-based interventions under COVID-19 constraints.